2019
DOI: 10.3928/00989134-20190430-01
|View full text |Cite
|
Sign up to set email alerts
|

Female Family Caregivers' Experiences During Nursing Home Admission: A Phenomenological Qualitative Study

Abstract: The experience of nursing home (NH) admission has a significant impact on older adults and their relatives. The aim of the current study is to describe the life experiences of female family caregivers ( N = 20) after long-stay NH admission of their relative. A qualitative phenomenological approach was followed with purposeful sampling. Data were collected over 18 months using unstructured interviews, letters, and diaries and were analyzed using systematic text condensation analysis. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…In most countries, the informal care of older people is primarily provided by women, who support older relatives to live independently for as long as possible (World Health Organization, 2015). Family members undertake caring for a multitude of reasons, most commonly being a sense of responsibility or emotional obligation reflecting long‐standing relationships; a belief that they can provide better care; or simply because no one else is available (Palacios‐Ceña et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most countries, the informal care of older people is primarily provided by women, who support older relatives to live independently for as long as possible (World Health Organization, 2015). Family members undertake caring for a multitude of reasons, most commonly being a sense of responsibility or emotional obligation reflecting long‐standing relationships; a belief that they can provide better care; or simply because no one else is available (Palacios‐Ceña et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Family carers may continue to visit their relative regularly, providing continuity, ensuring that their needs are maintained in their new ‘home’; and some remain actively involved in their care, providing social support and communicating with staff (Gaugler et al, 2003). These caregivers often feel that visiting their relative frequently maintains a sense of continuity but may also help to alleviate their own stress and provide validation for the decision to move their relative into residential aged care (Jacobson et al, 2015; Palacios‐Ceña et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not feeling welcome in RACF, being apprehensive or ill-informed about quality of care were adverse factors to carer’s adjustment [ 15 , 16 ]. Flow and transparency of information between carer and the facility staff, and staff support of regular visits prevented loneliness in the carers, and contributed to better mental health of carers [ 18 , 37 ]. Barken’s study reported the following from a participant: ‘ the more contact you have with the families even though it’s time- consuming, the more transparent you are, the more honest you are about the way things are here, you know, it’s really appreciated and the more on board families are ’.…”
Section: Resultsmentioning
confidence: 99%
“…I’m the familiarity of the past. But as far as physical care- I think I’m a lot of mental care, but no, no, there’s no physical care going on.’ Fewer visits of carers to the facility were also linked to significantly poorer relationships with staff [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%